Cerebrospinal Fluid Glucose and Lactate Levels After Subarachnoid Hemorrhage: A Multicenter Retrospective Study. Issue 2 (April 2020) - Taccone, Fabio S.; Badenes, Rafael; Arib, Safa; Rubulotta, Francesca; Mirek, Sebastien; Franchi, Federico; Gordon, Sara; Nadji, Abdelouaïd; Crippa, Ilaria A.; Stazi, Elisabetta; Bouhemad, Belaïd; Lozano Roig, Angels; et al.
Abstract : Background: In patients with subarachnoid hemorrhage (SAH), abnormalities in glucose and lactate metabolism have been described using cerebral microdialysis. Glucose and lactate concentrations in cerebrospinal fluid (CSF) are more easily accessible, but scarce data are available in this setting. The aim of this study is to assess the relationship of CSF glucose and lactate with blood concentrations and with unfavorable neurological outcome after SAH. Methods: A retrospective cohort study was conducted in 5 European University intensive care units. Patients aged 18 years and above who were admitted after a nontraumatic SAH over a 4-year period (2011 to 2014) were included if they had an external ventricular drain placed, daily analysis of CSF including glucose (±lactate) concentrations for 1 to 4 consecutive days, and concomitant analysis of glucose and lactate concentrations in the arterial blood. Results: A total of 144 patients were included in the final analysis (median age: 58 [49 to 66] y; male sex: 77/144). Median time from admission to external ventricular drain placement was 1 (0 to 3) day; median Glasgow Coma Scale on admission was 10 (7 to 13), and CT-scan Fisher scale was 4. A total of 81 (56%) patients had unfavorable neurological outcome at 3 months (Glasgow Outcome Scale ⩽3). There was a weak correlation between blood and CSF glucose ( r 2 =0.07, P =0.007), and between blood and CSF lactate levels ( r 2 =0.58, P <0.001) on day 1, which were not influenced by insulin therapy. The presence of shock and low CSF glucose/lactate ratio were the only independent predictors of unfavorable outcome. Conclusions: CSF glucose and lactate levels poorly correlated with blood concentrations. Low CSF glucose/lactate ratio was associated with poor neurological outcome. Abstract : Supplemental Digital Content is available in the text.